1984
DOI: 10.1002/1097-0142(19840515)53:10<2125::aid-cncr2820531022>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic sarcoma producing human chorionic gonadotrophin: Case report with immunohistochemical studies

Abstract: An osteogenic sarcoma occurring in a 22‐year‐old woman was found to be associated with production of a large amount of beta human chorionic gonadotrophin (B‐hCG). Pregnancy was excluded on the basis of a normal ultrasonogram and a proliferative type endometrium obtained by curettage. A homogenate of the tumor was strongly positive for B‐hCG while immunohistochemical staining of the tumor cells was strongly positive for B‐hCG and negative for pregnancy associated glycoprotein. These results indicate ectopic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 4 publications
(1 reference statement)
0
25
0
Order By: Relevance
“…The apparent association with tumour aggressiveness led some authors to suggest that β-hCG expression may be due to tumour dedifferentiation, but others have found that dedifferentiated cells in their patients did not reveal β-hCG expression. 5,6,10 In the current study, all of our patients with positive β-hCG expression had histologically high-grade tumours of the osteoblastic (three patients) and telangiectatic (two patients) subtypes. In the literature, three cases were of the osteoblastic subtype, two were of the chrondroblastic subtype, and one was of the telangiectatic subtype.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…The apparent association with tumour aggressiveness led some authors to suggest that β-hCG expression may be due to tumour dedifferentiation, but others have found that dedifferentiated cells in their patients did not reveal β-hCG expression. 5,6,10 In the current study, all of our patients with positive β-hCG expression had histologically high-grade tumours of the osteoblastic (three patients) and telangiectatic (two patients) subtypes. In the literature, three cases were of the osteoblastic subtype, two were of the chrondroblastic subtype, and one was of the telangiectatic subtype.…”
Section: Discussionmentioning
confidence: 47%
“…[1][2][3][4][5][6][7][8][9] The results of our preliminary study suggest that although the incidence of β-hCG expression in osteosarcoma patients may not be high, it raises the question of the possible use of this marker in a subgroup of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations